2009
DOI: 10.1029/2009ja014121
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical and simulation study of the contact discontinuities based on a Vlasov simulation code

Abstract: [1] Contact discontinuity (CD) is the simplest solution that can be obtained from the magnetohydrodynamics (MHD) Rankine-Hugoniot jump conditions. Due to the limitations of the previous kinetic simulation models, the stability of the CD has become a controversial issue in the past 10 years. The stability of the CD is reexamined analytically and numerically. Our theoretical analysis shows that the electron temperature profile and the ion temperature profile must be out of phase across the CD if the CD structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Tsai et al . [] used different ratios of T e / T i (0.33, 1.25, and 5) on the two sides of a CD in Vlasov simulations. It is apparent that the values of T e / T i in these simulations were quite different from the ratios of T e / T i in the observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsai et al . [] used different ratios of T e / T i (0.33, 1.25, and 5) on the two sides of a CD in Vlasov simulations. It is apparent that the values of T e / T i in these simulations were quite different from the ratios of T e / T i in the observations.…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al . [] also examined the steadiness of CD structure in MHD, the ion‐electron two‐fluid, and the Vlasov simulations. Their simulations indicated that the CD structure is steady under the out‐of‐phase profiles of the ion and electron temperatures and of the ion and electron thermal pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Elimination-of-the-roundoff-error (ERE) technique [21] eliminates the errors generated from the accumulation of roundoff error due to subtraction during the modeling process. If the result of A minus B is less than a defined value, the result of A minus B is set to be equal to zero in all the subtraction.…”
Section: Elimination-of-the-roundoff-error Techniquementioning
confidence: 99%
“…Therefore we use the four staged fourth-order Runge-Kutta method [22,21] to obtain the first three steps U 1 , U 2 , U 3 . The fourth-order Runge-Kutta method can be represented as…”
Section: Time Discretizationmentioning
confidence: 99%
See 1 more Smart Citation